STUDIES OF NOCARDIOSIS IN CATTLE 1 - ISOLATION OF NORCARIDA ASTEROIDES FROML MASTITIS IN CATTLE - Alwan, MJ.; Al Abaitii, A.S.; Barhoom, S.Sh. (The Iraqi Journal of Veterinary Medicine, 2022)
A six months survey (2-8/1994) was canied out to determine norcaiidal mastitis in cattle in certain dairy herds. A total 126 milk samples collected from mastitic‘ cows and milk tank. Of which 10 from Al-Khalis station, 15 from A1-Wahda station, 6 from White Good village, 90 from Al-Dejaila station and 5 fromMilktauk. Examination of the samples result in isolation of Norcaitlia asteroides from Al-Dejaila station. The results explained that 25 animals were positive for norcaridal infection with prevalence of 20.8 % of these 25 cases, 5 cases, in pure cultural and 20 cases, mixed with other organisms. Bacteriological examination of mill: tank also resulted in positive for norcaridial isolates. Metastasis to the lung and supramammary lymph node was demonstrated. The results also explained that norcardial isolates from mastitic cows were more virulent to guinea pigs, andthis study revealed that norcardial infection are not rare in cattle.